Scd-1 deficiency promotes the differentiation of CD8+ T effector - Lin, Yiwei; Li, Xushuo; Shan, Haojie; Gao, Jie; Yang, Yanying; Jiang, Linlan; Sun, Lu; Chen, Yuwen; Liu, Fangming; Yu, Xiaowei (Frontiers in Cellular and Infection Microbiology, 2024)
The impact of various fatty acid types on adaptive immunity remains uncertain, and their roles remain unelucidated. Stearoyl-CoA desaturase (Scd) is a Δ-9 desaturase, which is a key rate-limiting enzyme for the conversion of saturated fatty acids (SFA) to monounsaturated fatty acids (MUFA) in the fatty acid de novo synthesis. Scd-1 converts stearic acid (SA) and palmitic acid (PA) to oleic acid (OA) and palmitoleic acid (PO), respectively. In this study, through a series of experiments, we showed that Scd-1 and its resulting compound, OA, have a substantial impact on the transformation of CD8+ naïve T cells into effector T cells. Inactivation of Scd-1 triggers the specialization of CD8+ T cells into the Teff subset, enhancing the effector function and mitochondrial metabolism of Teff cells, and OA can partially counteract this. A deeper understanding of lipid metabolism in immune cells and its impact on cell function can lead to new therapeutic approaches for controlling the immune response and improving prognosis.